The Quest for Alternatives in Postcolonial African Fiction : A Study of Selected Novels by Ayi Kwei Armah - Benzahra Mustapha (Université Sidi Mohamed Ben Abdellah, Faculté des Lettres et Sciences Humaines - Dhar El Mahraz -, Fès, 2018)
The purpose of this work is to explore Ayi Kwei Armah’s quest for alternatives to the present-day socio-political impasse in Africa. He offers possibilities in his novels to re-build an ideal society. Thus, this research intends to address two major questions: What are the complex problems of postcolonial African society? And what are the cures Armah suggests to shape a good future for the continent? To come to terms with this purpose, this study examines The Beautyful Ones Are not Yet Born (1968), Fragments (1969) , Why Are We So Blest ?(1972) , Two Thousand Seasons (1973) , The Healers (1978 ) and Osiris Rising (1995) and KMT:In the House of Life (2002). To fully explore Armah’s quest for alternatives for a better society, this thesis is divided into three chapters and a conclusion. The first chapter gives a general overview about postcolonial African fiction. The survey shows that the main purpose of postcolonial African fiction is to interrogate colonialism and its effect and to search for renewal. Then, the chapter looks at some issues still preoccupying African literary writers and critics alike. The most serious concern is the language problem. The second chapter is an analysis of The Beautyful Ones Are Not Yet Born, Fragments, Why Are We So Blest?. It diagnoses the African reality to find out the ills of postcolonial West African nation. The chapter also examines the major features of Armah’s method in delivering his themes and his protest that permeates the early novels. These works portray the failure of independence to fulfill the promising expectations of the struggle for national independence. These novels are an expression of Armah’s own disillusionment with Ghana’s post-independent regime. The purpose of the third chapter is the examination of Two Thousand Seasons, The Healers, Osiris Rising and KMT: In the House of Life to identify Armah’s remedies for the postcolonial socio-political ailment. In the pursuit of their goal, all these works choose African history as a vehicle to articulate their artistic visions. The past is used in the present to build the future. The chapter also discusses the techniques used in these novels. They are revolutionary in both content and form. They have been unanimously designated as Armah’s resolution of the postcolonial African writer’s quest for a more authentic African mode of expression. The conclusion recapitulates all the chapters of this study. It shows that the curatives are the return to “the way”, the communal effort, positive role for African women, the unity of Africans, commitment, radical reform of education and the existence of true scholars. In addition to a critical assessment of the curative strategies, the conclusion also opens a new problematic.
Keywords: Littérature africaine; Postcolonial African Fiction; Study of Selected Novels; Ayi Kwei Armah